METAPHORICAL EXPRESSION IN MANADO MALAY - Kristian Rumengan; Deane J. Wowor; Tirza Kumayas (JELLT (Journal of English Language and Literature Teaching), 2020)
The purpose of this study is to identify the metaphorical expression in Manado Malay and also to describe the meaning of those metaphors. Metaphor is a kind of figurative language which uses connotative meaning through the comparison without using the word “like” or “as”. Most of metaphorical expression comes from a human behavior. The subject consisted of speakers of Manado Malay particularly the researcher himself and those who lives in Wuwuk village. The writer used descriptive research. Qualitative research is the suitable method to analyze the metaphorical expression. The writer used qualitative approach to find the actual data about metaphorical expression, the data collections are in the form of words, pictures, rather than numbers. The result shows that there are 53 metaphorical expressions in Manado Malay commonly used in everyday speech. It can be indicate by through, human's behavior, human's characteristics, and feelings, such as “Putar bale” which means someone who is lie and “Bobou seho” which means someone who has drunk. Some other metaphor is used to describe a circumstance such as, “ujang kopi” which mean zenithal rain or refer to the hot rainy weather conditions. It is expected that many other researches could be conducted especially the problem which concerned with metaphorical expression. Studying language and it’s relation with metaphorical expression leave many question to answer. That is why, by conducting this research, other researchers can get some information about metaphorical expression in Manado Malay